Intrahousehold welfare in rural Ethiopia - Fafchamps, Marcel; Kebede, Bereket; Quisumbing, Agnes R. (Wiley, 2009)
We examine the relationship between bargaining power and intrahousehold welfare in rural Ethiopia. The relative nutrition of spouses is associated with differences in cognitive ability, independent income and asset devolution upon divorce. Female empowerment benefits child nutrition and education. Spouses’ health, leisure and consumption of assignable goods show no association with differences in bargaining power. The relative nutrition and health of spouses varies across villages, but not in ways predicted by anthropological accounts of female empowerment. Bargaining variables may be weakly associated with intrahousehold welfare because surveyed households are poor and have little room for disagreement over consumption.